The crisis-response match: An empirical investigation - Sascha Raithel; Stefan J. Hock (Strategic Management Journal, 2021)
Prior crisis-response literature outlines zones of conformity (i.e., response meets stakeholder expectations), underconformity (i.e., response falls short of expectations), and overconformity (i.e., response exceeds expectations). We utilize a mixed-method approach to empirically test the impact of different response strategies on customers (Study 1: experiment) and investors (Study 2: event study). We not only find empirical support that a conforming strategy outperforms both nonconforming strategies concerning stakeholders' affective evaluations of reputation, but extend this proposition to stakeholders' cognitive evaluations of reputation and the financial implications for the firm. The most counterintuitive finding is that overconforming strategies result in lower firm reputation and stock returns relative to conforming strategies. Thus, exceeding stakeholder expectations during a crisis can have unintended negative consequences. Managerial Summary How should firms react to product recalls? Previous research suggests that exceeding expectations of external stakeholders should have a neutral or even positive impact on firm reputation and financial performance, while falling short of expectations should have a negative impact. In this article, we test the impact of different product recall strategies. The most counterintuitive finding is that exceeding stakeholder expectations during a product crisis can have unintended negative consequences on both customers and investors.
Keywords: 650; conformity; crisis; firm response; reputation; product recall; stock return